The digitization of processes in the organization as a competitive advantage in the Covid-19 context (Journal of Management & Business, 2021)
The unprecedented context presented by the covid 19 pandemic, implied a disruption in the managment of the organizations that abruptly found themselves before an unexpected scene and were compeled to redesign their learning models to adapt to it. The rules of the new normal accelerated the digitization of organizational processes, allowing many sectors of the economy to regenerate and even gain positions in the new economic order that was beginning to manifest itself. In this environment, two variables were identified as determinants: human capital and the degree of automation of administrative processes. This work willl present the conclusions obtained during the development of the qualitative research project titled «Emergent knowledge produced by the implementation of digital automation in organizational processes», linked to the aswers that Córdoba’s organizations gave to adjust to the changes and actívate their operation in the new scenario posed by the covid-19 pandemic.
Keywords: Digitization; competitive advantage; Covid-19 context